DESIGN AND OPERATING PRINCIPLE OF A SEMICONDUCTOR SENSOR FOR METHANE AND NATURAL GAS - Khudoyberdiyeva Sabina Murodjonovna; Eshobilova Mavjuda Ergashboyevna (Research Focus International Scientific Journal, 2025)
This paper presents the design and operational principles of a semiconductor-based gas sensor specifically engineered for the detection of methane (CH₄) and natural gas. The sensor operates on the principle of conductivity modulation in metal oxide semiconductors such as tin oxide (SnO₂), zinc oxide (ZnO), and tungsten oxide (WO₃), whose electrical resistance changes in response to gas adsorption on the sensor surface. The sensing element is integrated into a planar structure with a built-in microheater, allowing temperature control to optimize sensitivity and selectivity. Methane molecules are detected through redox reactions with chemisorbed oxygen species, resulting in measurable changes in resistance. The design includes signal conditioning circuits and data acquisition modules to enable real-time monitoring. The sensor demonstrates high sensitivity to low concentrations of methane, fast response and recovery times, and stable operation under varying environmental conditions.